THE DEVELOPMENT OF THE INNOVATION NANO COMPOSITE MATERIAL FOR UNMANNED AIRCRAFT VEHICLES - Galina Mikhaylovna Danilova-Volkovskaya; Alexander Arkadyevitch Begak (Современная наука и инновации)
This paper presents the investigations of innovation nanocomposite material to increase structural strength, reduce weight and provide radio transparency in unmanned aircraft vehicles. The method of the of creation of polymer nanocomposite that consists of thermosetting plastics matrix and complex fillers: of natural silica and carbon multi-layer nanotubes was designed.